Effect of Nightmare on Sleep Disturbance and Emotional Dysregulation among University Students - Naila Shakeel; Attiya Khan; Dr Sajid Mehmood Alvi (International Journal of Business and Economic Affairs, 2024)
This study investigated the effect of nightmare on sleep disturbance and emotional dysregulation among University Students.The sample size comprised of 300 students which include 150 males and 150 females. Data was taken from the different departments of Government Post Graduate College for boys and University of Haripur by using the purposive sampling technique. Three instruments were used to take the responses of the participants including Nightmare Experience Scale,Sleep Quality Scale and Difficulty in Emotion Regulation.The findings revealed that there is significant role of nightmare on sleep quality and emotional dysregulation. Findings indicates that there is significant mean difference between males and females on sleep disturbance and emotional dysregulation. Results proved that Rural area participants differ significantly on Sleep Disturbance and Emotional Dysregulation as compared to urban area participants. Outcomes of this research will be helpful in finding further aspects of nightmare on these variables.